Ekosistem Media Modern Melalui Modifikasi Penyiar Menjadi Influencer Di TVRI Bengkulu - Yuni, Yuni Puspita Sari; Gushevinalti; Neneng Cucu Marlina (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This research aims to explore the changes in the media ecosystem at TVRI Bengkulu brought about by the modification of broadcasters' roles into influencers within the context of modern media. This role transformation involves changes in how broadcasters interact with audiences and its impact on communication structures, work culture, and audience engagement in the digital world. The study employs a qualitative approach with a constructivist paradigm, utilizing in-depth interviews, observations, and document analysis related to TVRI Bengkulu's programs for data collection. The findings reveal that although broadcasters at TVRI Bengkulu have started using social media to build personal branding and engage with audiences, there are no formal regulations or policies supporting the development of this role. Nevertheless, broadcasters who have transitioned into influencers have successfully expanded their reach, particularly among the younger generation who are more active on social media. This transformation has impacted the media ecosystem at TVRI Bengkulu in terms of social interaction, content management, and shifts in work culture within the broadcasting organization. This study is expected to provide deeper insights into how the transformation of broadcasters into influencers influences the sustainability and relevance of broadcasting institutions in the digital era.